The Mexican Crisis and the Philippine Economy - Freedom from Debt Coalition, FDC - (Kasarinlan: Philippine Journal of Third World Studies, 2008)
The Mexican Crisis meant the loss of confidence of the foreign investors in the emerging markets. The growth of the Mexican economy was fueled by large infusions of foreign funds following the liberalization and opening up of its markets. Initially, Mexico possessed enough foreign reserves to keep inflation at bay. More importantly, this period of abundance tolerated the increasing trade and current account deficits. Signs of imminent danger were ignored; the availability of cheap imports continued to widen the trade gap between Mexico and its wealthier trading partners which, in turn, drained Mexico’s international reserves. As long as short-term capital acts as the backbone of an economy, the latter can never withstand the volatility of both the domestic and the international market. As the Philippines is currently in a state that is very similar to Mexico before the Crisis, the Philippine economy can very well follow the track of the Mexican economy; as long as the government sees no urgency and refuses to recognize this connection, believing instead that there can be growth under its present development paradigm, the Philippines can soon become another Mexico.